Utilization of Electronic Nose to Detect Quality of Meat in the Beef Ribs section - Hananto, Bayu; Widiyanto, Didit; Raafi'udin, Ridwan (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study analyzes the use of Electronic Nose (E-Nose) in detecting the quality of beef on the ribs. This experiment used a variety of gas sensors, and found a significant pattern related to rib meat quality. There are three sensors, namely MQ137, MQ5, and MQ6, which show the value is inversely proportional to the other sensors. An increase in the value of this sensor indicates a decrease in the quality of the ribs. Furthermore, MQ8 gave the highest score in the